(untitled) - HARJO WASKITO, REKSO (Language Horizon: Journal of Language Studies, 2015)
BahasaInggristelahmenjadibahasa international utama yang tersebar di penjurudunia.Jepang, Negara yang tidakpernahmengalamipenjajahanolehnegarabaratsecarasignifikanmenunjukanpenyebaranBahasaInggrismelalui music danbudayapopulernya (Stanlaw 2005). ONE OK ROCK sebuah band rock dariJepangdengan album Jinsei x Boku= di 2013 merupakancontohbagaimanaBahasaInggrismempunyaiperanpentingdalam album rock BahasaJepangterutamadalampenekanandanpe. LalustudiinibertujuanuntukmengetahuibagaimanaBahasaInggrisberkontribusidalamlirik album danbagaimanaBahasaInggrismempengaruhi album dalampenerimaan social.StudiinidilakukandengantujuanuntukmengetahuimotivasiBahasaInggrissebagaialatpenekanandalammusik rock Jepangmenggunakanteoridari James StanlawtentangPenjelasaandarimotivasiBahasaInggrisdalammusikJepang.Metodologi yang digunakanuntukmenganalisa data adalahdeskriptifkualitatifdimanapenelitimerupakan instrument utamadaristudiini, Patton, (2001) dan study inijugamenggunakanobservasidimanamelihattandapadakejadiantertentuNazir (1988).Dari hasilstudi, ditemukanbahwafitur-fiturpadamotivasiBahasaInggrismuculpadalagudenganBahasaInggris yang non-dominanpada album, sementarapadalagu yang dominandenganBahasaInggrismenunjukanfitur yang mucullebihsedikitdibandingkandengan yang mempunyaiBahasaInggris non-dominan. Dan padalagu yang mempunyaikeseluruhanBahasaInggrisfitur-fiturtersebutbahkankurangpenting, terlepasdaripenerimaansosialnya.Jadi, motivasiBahasaInggrisberdasarkanteoridariStanlaw (2005) efektifdalammempengaruhilaguberbahasaJepang, yang mempunyailirikBahasaInggris yang paling sedikit.Kata kunci:Kontakbahasa, alihkode, motivasiBahasaInggris, rock Jepang, musik.AbstractEnglish has become the major international language and spread across the world. Japan, a nation that never experienced colonization from western country is significantly showing the widespread of English through its popular culture and music (Stanlaw 2005). ONE OK ROCK a rock band from Japan with the album Jinsei x Boku= in 2013 is the clear example of how English take important role in the Japanese Rock album. One of the function of English in the album is as an Audacious device, and this study then are purposed to find out how English become the audacious device in this albumThe study was done in the purpose of knowing the English motivation in the Japanese rock music by using the theory of James Stanlaw about the explanation of English audacity in Japanese music. The methodology used to analyze the data is descriptive qualitative since the researcher is the main instrument of the study, Patton, (2001) and the study dealt with the kind of observation where looking at the occurrence of certain event Nazir, (1988). From the result of the study, it is found that the features of English audacity are present in the non-dominant English songs of the album, while in the dominant English songs the features that appear are less important than the non-dominant English. And in the full English songs the features are even least important aside from its social reception. So, the English motivation based on the theories of Stanlaw (2005) is effective to affect the Japanese rock songs, with the least English lyric in them.Key words:Language contact, code-switching, English motivation, Japanese rock, music.